Дефініювання словника й моделі категоризації - Старко, Василь Феодосійович; Starko, V. F. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано дефініції терміна словник, подані в науковій літературі, а саме розгорнуте визна¬чення Ж. Рей-Дебов, що наближається до точної класичної дефініції, визначення П. ван Стеркербурга, яке стосується лише нескорочених одномовних словників, та сформульоване з позицій когнітивної лінгвістики квазівизначення авторства Д. Герартса. До розгляду залучено словники нових типів. Установлено, що слов¬ни¬ки, аналізовані в сучасних працях, становлять природномовну категорію. Класична ж дефініція потребуватиме утворення певною мірою штучної категорії словників. The article analyzes the definitions of the term dictionary found in scholarly literature, in particular an extensive definition given by Josette Rey-Debove, which comes close to a strict classical definition, as well as two attempts to define a monolingual dictionary, one by by Piet van Sterkenburg and the other one by Dirk Geeraerts. The author shows that the definitions built on the classical model of categorization are unable to delineate the concept of the dictionary as such (this would require covering the entire variety of dictionaries) or even one specific time (a large monolingual dictionary). Geeraerts makes a distinction between a pretheoretical and theoretical concept of the dictionary. He shows that the former fits with the «prototypical» model of categorization, which includes members with different status and has blurry edges. The latter is yet to be formulated. To this end, a definition of the dictionary (or a dictionary type) needs to build in the form of a set of necessary and sufficient features (a classical definition). This definition will inevitably draw new category borders and will be artificial to a certain extent. The author analyzes new types of dictionaries, and the analysis confirms the idea that the pretheoretical concept of dictionaries fits with models of natural categorization.
Defining the Dictionary and Models of Categorization
Keywords: словник; dictionary; дефініція; definition; категоризація; categorization